Valences of Interdisciplinarity: Theory, Practice, Pedagogy - edited by Raphael Foshay (Cultural Dialectics, 2012)
The modern university can trace its roots to Kant's call for enlightened self-determination, with education aiming to produce an informed and responsible body of citizens. As the university evolved, specialized areas of investigation emerged, enabling ever more precise research and increasingly nuanced arguments. In recent decades, however, challenges to the hegemony of disciplines have arisen, partly in response to a perceived need for the university to focus greater energy on its public vocation-teaching and the dissemination of knowledge. Valences of Interdisciplinarity presents essays by an international array of scholars committed to enhancing our understanding of the theoretical underpinnings and the practical realities of interdisciplinary teaching and research. What is, and what should be, motivating our reflections on (and practice of) approaches that transcend the conventional boundaries of discipline? And in adopting such transdisciplinary approaches, how do we safeguard critical methods and academic rigour? Reflecting on the obstacles they have encountered both as thinkers and as educators, the authors map out innovative new directions for the interdisciplinary project. Together, the essays promise to set the standards of the debate about interdisciplinarity for years to come.